Checklist of the parasites of fishes of Latvia - Kirjusina, Muza (Food and Agriculture Organization of the United Nations, 2007)
The checklist summarizes information on the parasites of Latvia fishes contained in the world literature dating to the end of 2005. Information is presented in the form of parasite-host and host-parasite lists and includes 305 named of parasites, distributed among the higher taxa.